2012
DOI: 10.5665/sleep.1954
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Rhythms in Blood Cell Populations and the Effect of Acute Sleep Deprivation in Healthy Young Men

Abstract: Granulocyte levels and diurnal rhythmicity are directly affected by acute sleep deprivation; these changes mirror the body's immediate immune response upon exposure to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 31 publications
5
90
1
1
Order By: Relevance
“…The observed induction of HSPA1B during sleep deprivation is in agreement with previous work demonstrating its upregulation in obstructive sleep apnoea and diseaseassociated oxidative stress, and enhanced HSPA1B gene expression in several brain regions in mice during sleep deprivation (Lavie et al, 2010;Terao et al, 2003). Interestingly, a recent study on changes in the brain transcriptome upon sleep deprivation demonstrated that upregulation of HSPA1B in mice remains even if the corticosterone arm of the stress response has been eliminated (Mongrain et al, 2010 (Ackermann et al, 2012). Together, our data support the view that sleep deprivation can be regarded as a strong external stressor and immune challenge (Faraut et al, 2012;Mullington et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed induction of HSPA1B during sleep deprivation is in agreement with previous work demonstrating its upregulation in obstructive sleep apnoea and diseaseassociated oxidative stress, and enhanced HSPA1B gene expression in several brain regions in mice during sleep deprivation (Lavie et al, 2010;Terao et al, 2003). Interestingly, a recent study on changes in the brain transcriptome upon sleep deprivation demonstrated that upregulation of HSPA1B in mice remains even if the corticosterone arm of the stress response has been eliminated (Mongrain et al, 2010 (Ackermann et al, 2012). Together, our data support the view that sleep deprivation can be regarded as a strong external stressor and immune challenge (Faraut et al, 2012;Mullington et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…A detailed description of the study protocol and the initial screening phase including eligibility criteria have been reported previously (Ackermann et al, 2012). Briefly, study eligibility was determined by questionnaires, medical and physical assessment, and analysis of blood and urine samples.…”
Section: University Of Surrey (Uk) Ethical Approval Was Obtained Fromentioning
confidence: 99%
See 1 more Smart Citation
“…It supports the contention that sleep has biochemical/pathological significance and that it plays a fundamental role eliminating the body of toxins or pathological metabolites which accumulate during periods of physical activity or inactivity, consolidating memories, elevating the production of immunochemicals, and perhaps also changing the way in which memories of different levels of significance are stored [29].…”
supporting
confidence: 67%
“…due to variations of (i) the levels of proteins and/or other biologically significant moieties such as fatty acids, nucleosides, minerals and vitamins; (ii) theprevailing reaction conditions which influence the rate and completeness of such genetic and phenotypic reactions and pathological onset/ outcomes e.g. temperature, acidity, levels of minerals; (iii) the levels of thyroid, pituitary or adrenal hormones; and/or (iv) the precise way which stress acts upon the body to produce a spectrum of pathological correlates/metabolites [28].It supports the contention that sleep has biochemical/pathological significance and that it plays a fundamental role eliminating the body of toxins or pathological metabolites which accumulate during periods of physical activity or inactivity, consolidating memories, elevating the production of immunochemicals, and perhaps also changing the way in which memories of different levels of significance are stored [29].Sleep has an anti-inflammatory role upon cell function which assists the body's natural eliminatory process(es), mainly via the urinary tract and lymphatic ducts, to eliminate toxins and thereby optimise normal cell function [11,12]. This is supported by noting that the brain shrinks in size during periods of sleep [30].…”
mentioning
confidence: 58%